HUMAN PAPILLOMA VIRUS AND EPSTEIN-BARR VIRUS IN THE DIAGNOSIS AND CLINICAL COURSE OF CHRONIC HYPERPLASTIC LARYNGITIS - Виктор Дмитриевич Осипов; Галина Северьевна Суржикова; Сергей Николаевич Филимонов; Сатеник Аршавиловна Клочкова-Абельянц (Медицина в Кузбассе)
Objective – to study the presence and significance of human papillomavirus and Epstein-Barr virus in the development of chronic hyperplastic laryngitis and evaluate the effectiveness of immunomodulating therapy in the treatment of the disease.